Molecular dissection of hemizygote-dependent dominance of super-early flowering in soybean - Xin Xu; Yang Yu; Bingjun Jiang; Dong Cao; Lixin Zhang; Hongchang Jia; Xuegang Sun; Li Chen; Shan Yuan; Fulu Chen; Zefu Lu; Yanhong Liu; et al. (Crop Journal)
In plants, numerous non-Mendelian inherited dominant effects, including over-, incomplete-, and co-dominance, are frequently observed, yet they remain insufficiently understood. A novel phenotype has been identified in specific soybean transformants overexpressing a single 35S::GmFT2a copy: super-early flowering dominance is exclusively observed in hemizygotes, not in homozygotes. Homozygous individual exhibits siRNA-mediated DNA methylation, causing epigenetic transcriptional silencing, whereas no such effect occurs in hemizygotes. Intriguingly, two distinct rounds of DNA methylation establishment occur, each mediated by a different mechanism. The homozygotes that derived from the hemizygous mother plants carrying 35S::GmFT2a locus was associated with the initiation of CHH-context DNA methylation at 35S promoters mediated by 21 and 22 nucleotide (nt) siRNAs. Subsequently, 24 nt siRNAs contribute to additional CHG- and CG-context DNA methylation at 35S promoters during the homozygosity of genes in plants already homozygous in maternal lineage. Reducing DNA methylation levels can be achieved by generating a hemizygous genotype through a crossing experiment with a recessive genotype. This research has unveiled a phenomenon: hemizygote-dependent dominance resulting from transcriptional silencing in homozygote offsprings. It provides new insights into the molecular mechanism underlying dominant effects.